A forgotten spirit of commercial television? Co-productions between Finnish commercial television company Mainos-TV and socialist television - Pajala Mari (My University, 2022)
Finnish commercial television company Mainos-TV co-produced a string of documentary and entertainment programmes with television broadcasters in the USSR, Czechoslovakia, the GDR, Hungary and Poland in the 1970s and 1980s. This article asks what motivated Mainos-TV, a commercial television broadcaster in a non-socialist country, to collaborate with socialist television? Based on an analysis of published and archival sources (e.g. industry documents, memoirs, television programmes and press coverage), the article argues that Mainos-TV engaged with socialist television to secure its position at a time when the operation of commercial television was still quite restricted. Finnish foreign policy placed great importance on maintaining good relations with the neighbouring USSR. In this context, the leadership of Mainos-TV viewed its collaboration with socialist broadcasters as a way to strengthen the company’s position. International entertainment programmes and co-produced documentaries on social and cultural topics offered Mainos-TV ‘quality’ programming that differed from the stereotypical image of commercial television. Collaboration with Eastern European partners was not purely strategic, however, as it also brought influences from socialist television culture to Mainos-TV’s offerings. Mainos-TV’s co-productions with its socialist partners highlight the largely forgotten complexity of the history of European commercial television.